2011
DOI: 10.2139/ssrn.1973527
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Corruption in Russia: A Disaggregated Analysis

Abstract: This paper examines determinants of corruption across Russian regions. Key contributions include: (i) a formal study of economic corruption determinants across Russian regions; (ii) comparisons of determinants of perceived corruption versus those of actual corruption; and (iii) studying the influence of market competition and other factors on corruption. The results show that economic prosperity, population, market competition and urbanization are significant determinants of Russian corruption. The use of alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…These findings are, therefore, relevant to international institutions and policymakers that seek to adequately measure the intensity of corruption. Corruption indices typically rely on perception data which, if used without bias control, may give misleading results (Belousova, Goel, & Korhonen, 2014; Galtung et al, 2013; Olken, 2009). For instance, the Transparency International Corruption Index (Lambsdorff, 2005) or the World Bank Governance Indicators (Kaufmann, Kraay, & Mastruzzi, 2011) heavily draw on perception data (Olken, 2009).…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%
“…These findings are, therefore, relevant to international institutions and policymakers that seek to adequately measure the intensity of corruption. Corruption indices typically rely on perception data which, if used without bias control, may give misleading results (Belousova, Goel, & Korhonen, 2014; Galtung et al, 2013; Olken, 2009). For instance, the Transparency International Corruption Index (Lambsdorff, 2005) or the World Bank Governance Indicators (Kaufmann, Kraay, & Mastruzzi, 2011) heavily draw on perception data (Olken, 2009).…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%
“…In their insightful study, Dininio and Orttung (2005) demonstrated the diverse levels of regional corruption and tested the bestknown theories of corruption using a data-set measuring corruption in 40 Russian regions in 2003. Belousova, Goel, and Korhonen (2011) examined the role of economic factors as determinants of corruption, using the same data-set; Sharafutdinova (2010) applied these data to study the differences in experienced and perceived corruption; and Kolomak (2007) linked the spread of corruption to the administrative practices and bureaucratic procedures in Russian regions. Our study builds on this research using several new data-sets to analyze corruption in more than 60 regions of Russia in 2010.…”
Section: Russian Regions and The Federal Government's Anticorruption mentioning
confidence: 99%